Epidemiology and antifungal susceptibility of Candida species in a tertiary care hospital, Kolkata, India - Partha Bhattacharjee (Mazandaran University of Medical Sciences, 2016)
Background and Purpose: The incidence of fungal infection as well as candidemia has increased significantly, contributing to morbidity and mortality in the developed countries. The alarming increase in infections with multidrug resistant bacteria is due to overuse of a broad spectrum antimicrobials, which leads to over growth of Candida spp.; thus, enhancing its opportunity to cause the disease. A shift has been observed in the relative frequency of each Candida spp. Antifungal agents available for the treatment of systemic and invasive candidiasis are restricted to polyenes, allylamines, azoles, and the recent echinocandin class of molecules. In the past few decades, the incidence of resistance to antifungal treatment of Candida spp. has increased rapidly, which is of serious concern for healthcare professionals. Studies on prevalence of infections and antifungal susceptibility testing can help with deciding on clinical strategies to manage this problem. Herein, we aimed to identify the epidemiology of Candida spp. among blood culture isolates and to investigate the susceptibility pattern of these species to antifungal agents. Materials and Methods: Candida spp. were isolated from blood cultures from 70 patients in a tertiary care hospital, Kolkata, India. The growth of Candida spp. on sabouraud dextrose agar was confirmed by Gram staining, where grampositive budding fungal cells were observed. The species identification as well as antifungal susceptibility testing were performed with VITEK 2 compact automated system using VITEK-2 cards for identification of yeast and yeast-like organisms (ID-YST card). Antifungal susceptibility testing was carried out with VITEK 2 fungal susceptibility card (AST-YS07) kit. Results: Out of 70 samples, Candida albicans were isolated from 34 (48.57%) samples. The remaining 36 (51.43%) were non-albicans Candida (NAC). Out of 34 C. albicans, antifungal susceptibility was detected in 28 isolates, all of which were sensitive to fluconazole (FLC). Resistance to amphotericine B (AMP), flucytosine (5FC), voriconazole (VRC), and itraconazole (ITC) was observed in 44.12%, 52.94%, 8.82%, and 17.65% of the cases, respectively. For other Candida spp. (other than C. albicans), antifungal susceptibility was evaluated for 36 isolates, among which resistance to AMP, FLC, 5FC, VRC, and ITC was found in 30.56%, 61.11%, 33.33%, 19.44%, and 38.89% cases, respectively. Conclusion: Species-level identification of Candida and their antifungal sensitivity testing should to be performed to achieve better clinical result and to select an appropriate and effective antifungal therapy. High resistance to antifungal agents is an alarming sign to the healthcare professionals.